Penegakan Hukum Praktik Cornering The Market Pada Perdagangan Saham Di Pasar Modal - Frederick, Joshea (Universitas Sang Bumi Ruwa Jurai, 2024)
Cornering the Market is a form of violation of stock trading in the capital market. Cornering the Market. The practice of Cornering the Market violates the provisions of Article 91 and Article 92 of Law Number 8 of 1995 concerning the Capital Market. Under the provisions of Article 55 of Law Number 21 Year 2011 regarding the Financial Services Authority, as of 31 December 2012, the functions, duties and authority of regulating and overseeing financial services activities in the Capital Market sector of the Capital Market Supervisory Agency have turned to the Financial Services Authority. The main problem in law enforcement on the Cornering the Market case in stock trading in the capital market is the problem of proving the existence of the case. Cornering the Market is closely related to technological advances, because given the stock trading system is now using the online system, so to prove the violation is not easy. In addition, during this case if there is a case of Cornering the Market is often sanctioned not the perpetrators of Cornering the Market but securities companies and issuers in the form of administrative sanctions penalties and freezing of business activities and stock trading